Landslide Science for a Safer Geoenvironment Vol.1: The International Programme on Landslides (IPL) - Sassa, Kyoji; Canuti, Paolo; Yin, Yueping (Springer International Publishing : Imprint: Springer, 2014)
This volume contains peer-reviewed papers from the Third World Landslide Forum organized by the International Consortium on Landslides (ICL) in June 2014. The complete collection of papers from the Forum is published in three full-color volumes and one mono-color volume. This first full-color volume contains the following: Plenary lectures International programme on landslides Thematic and regional networks on landslides Policy, legislation, and guidelines on landslides Climate and landuse change impacts on landslides Recognition and mechanics of landslides General landslide studies Student sessions, landslide teaching tools, and other side events.